2016
DOI: 10.1038/srep32709
|View full text |Cite
|
Sign up to set email alerts
|

On the mobility, membrane location and functionality of mechanosensitive channels in Escherichia coli

Abstract: Bacterial mechanosensitive channels protect cells from structural damage during hypoosmotic shock. MscS, MscL and MscK are the most abundant channels in E. coli and arguably the most important ones in osmoprotection. By combining physiological assays with quantitative photo-activated localization microscopy (qPALM), we find an almost linear relationship between channel abundance and cell survival. A minimum of 100 MscL (or MscS) channels is needed for protection when a single type of channel is expressed. Unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 53 publications
5
26
1
Order By: Relevance
“…Although all these studies suggest cluster formation for native channels, the debate around this question is still open. A recent study, through use of PALM (photo-activated localization microscopy) and SPT (single particle tracking), had shown strong indications that labeling with fluorescent molecules predisposes MscL channels to form clusters [34]. In either case, if there is any form of channel aggregation in bacterial cells, the collective phenomena we describe here may be directly relevant for the osmotic response of bacteria.…”
mentioning
confidence: 95%
“…Although all these studies suggest cluster formation for native channels, the debate around this question is still open. A recent study, through use of PALM (photo-activated localization microscopy) and SPT (single particle tracking), had shown strong indications that labeling with fluorescent molecules predisposes MscL channels to form clusters [34]. In either case, if there is any form of channel aggregation in bacterial cells, the collective phenomena we describe here may be directly relevant for the osmotic response of bacteria.…”
mentioning
confidence: 95%
“…Driven by membrane tension, the helices are thought to tilt with respect to one another, creating a space between them (up to 3 nm in diameter) for small solutes to non-selectively pass through [15]. Recent studies debate the existence and the role of spontaneous clustering of one of the MSCs found in Escherichia coli, MSC of large conductance (MscL) [16,17]. Indeed, membrane clustering appears to be a common mechanism in cellular signaling, and has been observed for many transmembrane proteins and signaling receptors [18].…”
mentioning
confidence: 99%
“…Clustering of MSC in vitro has been shown to result in collective, non-linear gating behavior [16], suggesting that it could tamper with cell's passive response during a hypoosmotic shock recovery. However, assessing the extent of MscL aggregation via imaging techniques in vivo has proven to be difficult due to the potential artifacts of the MscL tags on the process [17], and hence opens a need to explore orthogonal ways to investigate the aggregation phenomenon. Here, by developing a minimal computer model of MSCs embedded in a fluid membrane, we investigate the physical mechanisms behind the MSC cluster formation and cooperative gating, and their implications on cell-volume regulation.…”
mentioning
confidence: 99%
See 2 more Smart Citations